2009
DOI: 10.5194/nhess-9-895-2009
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater processes in a complex landslide, northern Apennines, Italy

Abstract: Abstract. The hydrogeological characteristics of rototranslational slides in flysch are complex, due to the inherent anisotropy and heterogeneity of rock masses and related deposits. The paper deals with the hydrogeological characterization of a reactivated roto-translational slide affecting Cretaceous flysch rocks, located in the northern Apennines of Italy. Continuous monitoring of groundwater levels, in-situ permeability and pumping tests, hydrochemical and physical analyses and Uranine tracers were the ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 14 publications
2
20
0
1
Order By: Relevance
“…Due to the continuous pumping in WA, the unconfined aquifer hosted in the head zone was progressively renewed by the inflow of more fresh and less mineralised water from the upper landslide body. This presence was confirmed by Ronchetti et al (2009) after conductivity loggings in P1: the authors detected a rapid increase of GW EC with depth (stabilised at about 4000 µS cm −1 at 20 m below GW L ). The undisturbed flysch aquifer suffered by the hydrological changes of the head zone: in sampling points P1 and DrA, Cl − contents were halved.…”
Section: Origin Of Groundwater and Deep Water Inflowmentioning
confidence: 52%
See 1 more Smart Citation
“…Due to the continuous pumping in WA, the unconfined aquifer hosted in the head zone was progressively renewed by the inflow of more fresh and less mineralised water from the upper landslide body. This presence was confirmed by Ronchetti et al (2009) after conductivity loggings in P1: the authors detected a rapid increase of GW EC with depth (stabilised at about 4000 µS cm −1 at 20 m below GW L ). The undisturbed flysch aquifer suffered by the hydrological changes of the head zone: in sampling points P1 and DrA, Cl − contents were halved.…”
Section: Origin Of Groundwater and Deep Water Inflowmentioning
confidence: 52%
“…For instance, deep water upflow along regional tectonic structures can affect groundwater balance on a slope scale (Tóth, 2009). The presence of deep water into landslide deposits was reported in several cases in the northern Apennines (Colombetti and Nicolodi, 1998;Bertolini and Gorgoni, 2001;Ciancabilla et al, 2004;Baraldi, 2008;Ronchetti et al, 2009) as well as in other mountain chains (Bonzanigo et al, 2001;de Montety et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In the Alps or in the northern Apennines, most deepseated landslides occur in crystalline bedrocks (Barla and Chiriotti 1995;Agliardi et al 2001;Ronchetti et al 2009). The hydrological response of a fractured-rock slope depends on the geometry and hydraulic connectivity of the discontinuity network, on individual discontinuity properties, and on the intact rock properties (Maréchal 1998;Cappa et al 2004;Bogaard et al 2007).…”
Section: Introductionmentioning
confidence: 98%
“…Consequently, recent studies focus on indirect methods such as hydrochemistry surveys by monitoring springs for natural and artificial tracers (Bogaard et al 2007). For example, recent studies have demonstrated that the recharge area of a landslide can be larger than the landslide itself (Guglielmi et al 2002) or that the landslide groundwater variations can be significantly controlled by deep groundwater flows (Ronchetti et al 2009). In addition, hydrochemical methods can discriminate waters which flowed through the stable rock masses from those which flowed through the unstable rock masses (Binet et al 2009).…”
Section: Introductionmentioning
confidence: 98%
“…The landslide is a flysch rock slide, and is of a type quite common in northern Apennines. Previous studies(Berti et al, 2017;Ronchetti et al, 2009) indicated that, despite its complexity, the flysch behaves 7 Earth Surf. Dynam.…”
mentioning
confidence: 99%